PUSAT OLAHRAGA TINJU DI MAKASSAR PENERAPAN ARSITEKTUR FUTURISTIK - Bahri, Syamsul; Arfan, Taufik (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
Sports boxing center in Makassar will become a place that has full facilities for boxing fans to watch live matches as well as a place for athletes to gain a science of boxing. Activity center boxing as Landmark new in Makassar by applying the concept of display design the future, namely the emphasis display architecture Futuristic building and supporting facilities will be a public appeal to fill holiday time , with the structure approach Pneumatic will meet the application of the future design and became home the organizations, either directly from the government or a stand-alone mutual interest in order to facilitate communication.